Mental imagery, emotion and psychopathology across child and adolescent development. - Burnett Heyes, S; Lau, J; Holmes, E (2013)
Mental imagery-based interventions are receiving increasing interest for the treatment of psychological disorders in adults. This is based on evidence that mental imagery potently influences the experience of emotion in non-clinical samples, and that a number of psychological disorders are marked by syndrome-specific, distressing abnormalities in mental imagery. During childhood and adolescence, neurocognitive development impacting mental imagery processes may moderate its relationship with clinically-relevant emotional symptoms at a number of potential loci. Crucially, these changes could impact vulnerability to distressing mental imagery and the efficacy of mental imagery-based clinical interventions. This review synthesises evidence pertaining to developmental changes in the role and content of mental imagery, and in the cognitive sub-processes required to generate and sustain mental images. Subsequently, we discuss implications for understanding the developmental relationship between mental imagery, emotion and psychopathology. Translational cognitive neuroscience research investigating the content, emotional impact and neurocognitive substrates of mental imagery across development may reveal insights into trajectories of vulnerability to symptoms of a number of psychological disorders. If proper consideration is given to developmental factors, techniques based on mental imagery may be valuable as part of a treatment armoury for child and adolescent clinical populations and those at risk of emotional disorders.